Penentuan Kode Mutu Berbagai Jenis Kayu di Kebumen Berdasarkan SNI 7973:2013 - Izzudin, Muhammad; Pamungkas, Tri Wahyu; Hantoro, Reinaldy Dwi (Jurnal Teknik Sipil dan Lingkungan, 2024)
This research is determination of the reference strength for various types of wood that are widely used in Kebumen. The determination of the strength of the wood reference strength intended is the calculation of the modulus of elasticity based on the density of mass and moisture content obtained from the measurement of the volume of the wood sample, the initial weight before oven and the final weight after oven. The modulus of elasticity of wood is calculated using the formula contained in SNI 7973:2013. By getting the modulus of elasticity, we can immediately determine the quality code, for Bengkirai wood we get E = 13,041 Mpa which means that the wood has a quality code of E13 and the quality code on it is E14. By using the reference of the two quality codes, we can see and interpolate so that we can get the reference value of wood, namely bending strength (Fb) 12,02 Mpa, tensile strength (Ft) 10,60 Mpa, compressive strength parallel to the fiber (Fc) 10,60 Mpa, shear strength (Fv) 1,42, compressive strength perpendicular of the fiber (Fc? 2,83 Mpa), modulus of elasticity (E) 13.280 Mpa, minimum modulus of elasticity (Emin) 6.640 Mpa. In the same way, the strong value of other wood reference designs can be determined. In addition, from the results of the study, it was obtained that the highest elastic modulus of wood growing in Kebumen was Teak 12,972 Mpa (E12) while the highest elastic modulus of wood from outside Kebumen was bengkirai 13,280 Mpa (E13). The lowest modulus of elasticity is Javanese sengon wood 6,588 Mpa (E6)